(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
In the article are analyzed and summarized the views of Ukrainian and foreign linguists regarding the content of the concepts of “resultative”, “stative”, “passive”, “perfect tense”; are investigated qualification and differential criteria of the Ukrainian and Russian resultative, stative, passive, perfect tense; are defined the peculiarities of resultative designs.